The Strategies of Human Resource Administration in School Accordance in Buddhist - et. al., Phrakrukosolpariyattayanukij (Tharueti Rungchaiwitoon), (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of the article was to propose the strategies of human resource administration in school accordance in Buddhism. Documentary study was used for the design, and data was analyzed using content analysis and summarized by descriptive writing. Results of the study showed that new human resource management strategy is the strategy for human resources management in order to make the employees have the performance and behavior to meet the target and the organizational strategy. New role of human resource management must have both a role in shaping the strategy and its role in deploying the organization's strategy to human resources management. It is important to study the principles of Buddhism in relation to the administration of personal affairs that is the principle of Brahmaviharadham IV in order to study mercy management, to study the administration, to study management according to the principle of empathy, and to study the management based on the principle of happiness with focus on personnel administration of educational institution administrators. The concept of management was integrated between western concept and the principle of Brahmaviharadham IV. For a person who is a leader in Buddhism, is to know how to manage the principles and useful methods used as part of the administration. In the development of the work of personnel management in schools requires the use of Buddhist principles as a guide to the direction and direction of management to achieve both the efficiency and effectiveness of the work. If this principle is applied in the management, it will create a good relationship add to the unity by applying Brahmaviharadham IV to the administration of the school according to Western theories. These two principals have the same purpose to administer the school with integrity, to be willing, satisfy and work happily in the organization.